Revendo a Distinção Constatativo/Perfomativo - Costa, Claudio Ferreira (Princípios: Revista de Filosofia (UFRN), 2010)
In this paper is developed a reconstructive analysis of the conditions for both utterances constative and performative. These conditions were not presented by Austin (in that way), but we must deal with them, if we want that the distinction works. Under the light of this analysis is shown -against Austin -no compelling ground for the rejection of the distinction.